2018
DOI: 10.1177/2374373518788851
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Behavior to Oral Health of 456 Patients Who Presented for Tooth Extraction at 2 Health Facilities in Southwestern Nigeria

Abstract: Introduction: Tooth loss can indicate the population’s oral health situation; majority of patients presenting for tooth extraction have poor oral health behavior and dental service utilization. Understanding the factors responsible for the poor attitude may help in designing targeted intervention to improve their oral health behavior. This study aims to find out the effects of dental health attitude and behavior on tooth mortality in a cohort of adults attending the oral surgery clinic for tooth e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 7 Socioeconomic disparities and poor oral health habits appear to be part of the major factors responsible for dental extractions. 8 Previous studies showed that the socioeconomic status of the teenagers and their parents’ oral health-related beliefs predicted their oral health-related beliefs, which in turn predicted their use of toothbrushes and dental services. Moreover, there was an association between dental service use and untreated caries and missing tooth surfaces in adulthood, and a negative correlation between the number of untreated caries and missing tooth surfaces and OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Socioeconomic disparities and poor oral health habits appear to be part of the major factors responsible for dental extractions. 8 Previous studies showed that the socioeconomic status of the teenagers and their parents’ oral health-related beliefs predicted their oral health-related beliefs, which in turn predicted their use of toothbrushes and dental services. Moreover, there was an association between dental service use and untreated caries and missing tooth surfaces in adulthood, and a negative correlation between the number of untreated caries and missing tooth surfaces and OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that the decision to seek care through a particular process or from a particular provider is influenced by a variety of factors such as socioeconomic status (SES), sex, age, severity and type of illness, access to services and perceived quality of the service [ 6 8 ]. Besides, geographic location, family size, educational status, and cultural factors are influencers of oral health-seeking decisions in Nigeria [ 8 11 ]. The process of decision making for healthcare is complicated and might entail seeking the counsel of friends and family members, weighing potential risks and benefits, and forgoing other types of consumption that can be financed with resources used to purchase oral health care [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that significantly affect health-seeking behavior during illness episodes and also, the utilization of the formal or informal oral healthcare facilities and self/home care remedies by individuals seeking oral health care, have been described in several studies [5][6][7]. These studies have shown that the decision to seek care through a particular process or from a particular provider is influenced by a variety of factors such as socioeconomic status (SES), sex, age, severity and type of illness, access to services and perceived quality of the service [6][7][8]. Besides, geographic location, family size, educational status, and cultural factors are influencers of oral health-seeking decisions in Nigeria [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research [7][8][9] have discussed the variables that signi cantly in uence people's health-seeking behaviour during disease episodes, as well as how often they use formal or informal oral healthcare facilities and self-care or home remedies. These studies have demonstrated that a number of variables, including socioeconomic status, sex, age, the severity and type of illness, access to services, and perceived service quality, can affect a person's decision to seek care through a particular process or from a particular provider [8][9][10]. In addition, marital status, educational attainment, occupation, and health belief all affect decisions regarding utilising oral healthcare in Malaysia [11].…”
Section: Introductionmentioning
confidence: 99%